2004
DOI: 10.7773/cm.v30i2.179
|View full text |Cite
|
Sign up to set email alerts
|

Lower Cretaceous Alisitos Formation at Punta San Isidro: Coastal sedimentation and volcanism

Abstract: The Lower Cretaceous (Aptian-Albian) Alisitos Formation is well exposed at Punta San Isidro and adjacent sea cliffs on the Pacific shores of Baja California near Eréndira, Mexico. Continuous coastal outcrops define a local stratigraphic succession less than 100 m in total thickness, including repetitious tuff, sandstone and conglomerate units interbedded with discontinuous limestone beds rarely more than 2.5 m thick. The limestone beds are biostromal units that include scattered oysters and/or corals, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…This suite is made up of volcanic rocks with a relatively high proportion of felsic members (>63% SiO 2 ), volcaniclastic rocks, and a regionally extensive shallow water limestone unit (Allison 1974;Gastil et al 1975;Sedlock 2003;Busby et al 2006). Its stratigraphic thickness is estimated as 7.5 km (Allison 1974;Beggs 1984;Almazán-Vázquez 1988;Payne et al 2004), and the oldest reported UPb zircon age is 127 ± 5 Ma (Silver et al 1969) from a tuff sample located near Punta Cabras (locality 4; Figure 1a). This indicates that the age range of the Alisitos Group is highly similar to that of the Santiago Peak Volcanics (e.g.…”
Section: Geological and Structural Frameworkmentioning
confidence: 99%
“…This suite is made up of volcanic rocks with a relatively high proportion of felsic members (>63% SiO 2 ), volcaniclastic rocks, and a regionally extensive shallow water limestone unit (Allison 1974;Gastil et al 1975;Sedlock 2003;Busby et al 2006). Its stratigraphic thickness is estimated as 7.5 km (Allison 1974;Beggs 1984;Almazán-Vázquez 1988;Payne et al 2004), and the oldest reported UPb zircon age is 127 ± 5 Ma (Silver et al 1969) from a tuff sample located near Punta Cabras (locality 4; Figure 1a). This indicates that the age range of the Alisitos Group is highly similar to that of the Santiago Peak Volcanics (e.g.…”
Section: Geological and Structural Frameworkmentioning
confidence: 99%
“…Palmer is reported to form biostromes in unit 12 of the local stratigraphic section (Payne et al, 2004). This recumbent rudist characterizes the middle Albian Fredericksburg Group in Texas and northern Mexico (Scott and Filkorn, 2007;Scott & Gonzáles León, 1991) and is dated at 107.34-103.92 Ma (Scott, 2014).…”
Section: South Of Punta China At Punta San Isidro Caprinuloidea Perfectamentioning
confidence: 96%
“…The volcano-sedimentary rocks of the Lower Cretaceous Alisitos Formation are well exposed in the western margin of the Baja California peninsula (Busby, 2004). Previous studies have investigated palaeontology, stratigraphy, and depositional environments of the Alisitos Formation (Allison, 1955a;Allison, 1955b;Allison, 1974;Beggs, 1984;Beltramo, 2003;Busby, 2004;Gastil, Philips, & Allison, 1975;Masse, Beltramo, Martinez-Reyes, & Arnaud-Vanneau, 2007;Payne, Johnson, & Ledesma-Vazquez, 2004;Santillan & Barrera, 1930;Silver, Stehli, & Allen, 1963;Wetmore et al, 2005). Recently, Madhavaraju, Löser, Lee, Lozano-SantaCruz, and Pi-Puig (2016) carried out a geochemical study on limestone samples from the Punta China section, Baja California in order to identify the source of rare earth elements (REEs) and paleo-redox conditions.…”
mentioning
confidence: 99%
“…(Helenes, 2000). La Formación Alisitos, aflora en los alrededores del Rancho Alisitos al sureste de El Rosario en Baja California (Santillán y Barrera, 1930), está constituida por rocas volcánicas, volcaniclásticas, metavolcánicas, metasedimentarias y caliza (Payne et al, 2004) y se propuso un ambiente en el depósito someros sublitoral, incluyendo facies arrecifales (Allison, 1963). Fue fechada como Aptiano-Albiano en base a fauna marina (Allison, 1974 (Main, 1950).…”
Section: Formación Tlayúaunclassified